Acute toxicity and chromosomal aberration toxicity of insect wax and its policosanol - Jinju Ma; Kun Li; Wenwen Zhang; Liyi Ma; Juan Xu; Lanxiang Liu; Xiaoming Chen; Hong Zhang (Food Science and Human Wellness)
An acute toxicity test in Sprague Dawley (SD) rats and a chromosomal aberration toxicity test in Chinese hamster lung (CHL) fibroblasts were conducted to promote the application of insect wax and its policosanol. Results of oral acute toxicity test showed that the LD50 values of insect wax and its policosanol were higher than 5000 mg/kg. The rats showed no obvious toxic symptoms and survived, suggesting that these substances were not toxic. The chromosomal aberration rates of the CHL cells incubated with insect wax for 3–6 h under metabolic activation conditions and for 3–6 h and 24 h under non-metabolic activation conditions were lower than 5%. No significant difference was found compared with the negative control group. Also, no significant difference in chromosomal aberration rates was found between each dose group of policosanol under metabolic or non-metabolic activation conditions and the negative control group. Therefore, the chromosomal aberration rates of CHL cells treated with insect wax and its policosanol were negative regardless of metabolic activation conditions. These results indicate the absence of acute toxicity and potential chromosomal aberration in the tested dose range of insect wax and its policosanol.